2018
DOI: 10.1002/jclp.22626
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the MHC‐SF: An integration of the existing measurement approaches

Abstract: The structure of the MHC-SF is best represented as combination of the bifactor and ESEM model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 40 publications
11
25
1
Order By: Relevance
“…However, not surprisingly, SWB had the lowest internal consistency and composite reliability of the three subscales across samples, in line with most nonclinical (e.g. Hides et al, ; Keyes et al, ; Petrillo et al, ; Rogoza et al, ) and recent clinical findings (Franken et al, ; van Erp Taalman Kip & Hutschemaekers, ) and probably due to the aforementioned heterogeneity of the SWB subscale.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…However, not surprisingly, SWB had the lowest internal consistency and composite reliability of the three subscales across samples, in line with most nonclinical (e.g. Hides et al, ; Keyes et al, ; Petrillo et al, ; Rogoza et al, ) and recent clinical findings (Franken et al, ; van Erp Taalman Kip & Hutschemaekers, ) and probably due to the aforementioned heterogeneity of the SWB subscale.…”
Section: Discussionsupporting
confidence: 73%
“…Considering well‐being under a broader perspective, it is noteworthy that only few nonclinical studies (Joshanloo et al, ; Keyes et al, ; Lamers et al, ; Lupano Perugini et al, ; Petrillo et al, ; Rogoza et al, ) have specifically reported MHC‐SF subscale means, thereby permitting assessment of their relative sizes with respect to cultural, societal, political and economic context. Interestingly, SWB consistently had the lowest means of the three subscales in all nonclinical samples, including the present one.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations